Re-Interpretasi Hadis Tarbawi Tentang Kebolehan Memukul Anak Didik - Imron, Ali (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
In addition to offering a new interpretation of hadis that allows violence in the prayer education also shows that the main spirit as the practice of the prophet is prioritizing education by wise and gentle demeanor, not violence. Here it is also proved that, in practice, the Prophet never used force in educating his Companions, but rather gently proved and profound influence in the their souls.